Assessing Australia’s Progress towards a National Digital Communications Strategy at December 2022 - TelSoc Broadband Futures Group (Journal of Telecommunications and the Digital Economy, 2023)
This report, prepared by a working group of TelSoc, examines the progress during 2022 towards a national Digital Communications Strategy in Australia, using TelSoc’s report on the need for such a strategy, first published in 2020, as a basis for the dimension upon which progress might be measured. TelSoc made a similar assessment of progress in 2021. The progress assessment is an important public statement that reflects TelSoc’s beliefs in reporting and accountability in this important area of public policy.